If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(8b) = 8x + -1 Remove parenthesis around (8b) f * 8b = 8x + -1 Reorder the terms for easier multiplication: 8f * b = 8x + -1 Multiply f * b 8bf = 8x + -1 Reorder the terms: 8bf = -1 + 8x Solving 8bf = -1 + 8x Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '8f'. b = -0.125f-1 + f-1x Simplifying b = -0.125f-1 + f-1x
| 8w-6w=50 | | h+1.5=0.5 | | (12/52)(11/51) | | -13=x-18 | | 6/5(k-35) | | y=5(0.82)^(t/5) | | -14=7/9k | | X-6=-56 | | 3.6d=20.52 | | 9/4=x/16 | | 54/-36 | | Y=3+-1.5x | | -36/54 | | p+21=30 | | 5/3x-6=94 | | 6x/2/3 | | C=6/5(k-35) | | 10x^2/8 | | -6x-43=17-11x | | 3(2*x)+5x=11 | | -2=-19+9 | | -5.6(x-3.25)=22.4 | | 7x-19=15+5x | | 6=5/3b | | 8x=1/2(x-12) | | 30-(x+5)=7x-7 | | 2m+4=3m+2 | | 7x^2+5=54 | | -20+6x=12+4x | | -6k=90 | | 3-11x=-9 | | x-144=-12x+116 |